Pandangan Hukum Keluarga Islam Terhadap Kesantunan Berbahasa Mahasiswa Prodi Tadris Bahasa Indonesia: Tinjauan Pragmatik - Angraini Lubis, Anita; Parwis Halim Harahap, Muhammad (Jurnal Hata Poda, 2022)
The purpose of this study was to see the politeness level of Tadris Indonesian language students at UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan. The study in this research is also related to the views of Islamic family law and combined with a pragmatic review of the language. The research methods and techniques used are descriptive qualitative methods. The data collection technique is in the form of participatory observation. Data analysis techniques use interactive models, which are divided into three parts, namely data reduction, data presentation, and drawing conclusions. The results of this study are through a review of Islamic family law and a combination of pragmatic linguistics, it can be drawn the parameters of one's language politeness. Through various maxims that are directly or indirectly uttered by speakers in certain situations and speech contexts. After the various politeness maxims are applied, namely the maxim of wisdom, the maxim of modesty, the maxim of appreciation, the maxim of agreement, and the maxim of sympathy. Then, we will be able to use it as a benchmark and parameter for achieving good, correct, polite, and polite speech.Keywords: Islamic Family Law, Indonesian Department Students, Language Politeness